A Guide to Developing a Mainstreaming Program for Preschool Children Who Are Hearing Impaired Project CHIME - Nassau County Board of Cooperative Educational Services, Westbury, NY.; Pucciarelli, Catherine S.; Nassau County Board of Cooperative Educational Services, Westbury, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
Project CHIME (Children with Hearing Impairments in Mainstreamed Environments) was created to develop and implement strategies that promote effective mainstreaming of preschool hearing-impaired children, aged 2-5. This guide reviews issues that should be addressed before beginning a mainstreamed program, such as: funding; advance planning; staffing; philosophy; informing parents; establishing eligibility criteria; selecting a site; training staff and parents; scheduling the mainstreaming experience; and determining what services will be provided, such as an auditory trainer, speech therapist, psychologist, etc. Materials appended to the guidebook include a trouble shooting checklist on caring for hearing aids, a preschool classroom observation form, a worksheet for evaluating hearing-impaired preschool interaction, and a parent survey. (JDD)
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Contract Number: G008401386.
ERIC Note: A product of the Division of Special Education Program for the Hearing Impaired. For related documents, see 211 057-058.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Demonstration Programs; Educational Innovation; Educational Planning; Hearing Aids; Hearing Impairments; Intervention; Mainstreaming; Preschool Children; Preschool Education; Program Development; Early Intervention; Guides, Non-Classroom.; Tests/Questionnaires.